2010
DOI: 10.1103/physrevb.81.245427
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy contrast in lateral Ge-Si nanostructures onSi(111)3×3-Bi

Abstract: We investigate the origin of scanning tunneling microscope ͑STM͒ contrast in lateral Ge-Si nanostructures prepared on the Si͑111͒-ͱ 3 ϫ ͱ 3-Bi surface ͓M. Kawamura, N. Paul, V. Cherepanov, and B. Voigtländer, Phys.Rev. Lett. 91, 096102 ͑2003͔͒. At low sample bias, the voltage-dependent apparent height difference between Si-and Ge-terminated areas in STM images corresponds exceptionally well to the difference in voltageintegrated scanning tunneling spectroscopy ͑STS͒ curves measured in Si-and Ge-terminated area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…2. Surface termination with bismuth allows to distinguish between Si and Ge atoms, 27,28 but that would alter the surface reconstruction. The (111)-7 × 7 reconstructed "peninsula" in Fig.…”
Section: 1011mentioning
confidence: 99%
“…2. Surface termination with bismuth allows to distinguish between Si and Ge atoms, 27,28 but that would alter the surface reconstruction. The (111)-7 × 7 reconstructed "peninsula" in Fig.…”
Section: 1011mentioning
confidence: 99%
“…Sb and Bi are among the most popular surfactants used to control the growth mode of Si and Ge on Si(111) [5,6]. Moreover, by using Bi as a terminating layer on a Ge/Si(111) surface, it is possible to distinguish between Si and Ge topmost layers through a scanning tunneling microscope (STM) [2,7,8]. This unique property enabled the successful production of self-assembled Ge/Si nanostripes and nanorings in a controlled manner [2], and has become critical to the monitoring of the formation/evolution of small Ge clusters on Biterminated Si(111) surfaces by means of STM [9].…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in [10], at low applied voltages, ⎯3.0 V < U < +3.0 V, the main contribution to the tun neling current is determined by both the local density of electronic states of the surface and the height of the tunnel barrier, which can be described in terms of the decay length of local density of electronic states λ. According to [21], the tunneling current I through the tip of the scanning tunneling microscope at the height h over the surface can be represented in the form (1) where ν is the local density of electronic states of the surface, E is the energy of electrons, and integration is performed within eU above or below the Fermi level E F depending on the polarity of the applied voltage.…”
mentioning
confidence: 97%
“…A scanning tunneling spectroscopy study of the system Ge/Si(111) in the presence of Bi was recently reported [10]. In particular, the experiments showed that the contrast observed when electrons tunnel from the tip of the scanning tunneling microscope to empty electronic states of the surface is much larger than the contrast observed when electrons tunnel from the occupied electronic states of the surface to the tip.…”
mentioning
confidence: 98%